Sang Hyang Smara dan Dewi Ratih dalam Kakawin Smaradahana (Perspektif Gá¹›hastha AÅ›rama) - Mardiasni, Ni Kadek (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Kakawin smaradahana tell story of the burning of Sang Hyang Smara through the third eye of Bhaá¹ara Siwa and tell romance story of sang hyang smara and dewÄ« ratih. This Kakawin smaradahana contains the main noble values containing the teachings of love, namely the romance through the characterization of Sang Hyang Smara and Dewi Ratih. This romance of love is connected to a Hindu marriage, a teaching about Gá¹›hasta AÅ›rama or household life. The Gá¹›hastha AÅ›rama is a heredity in family life. The Gá¹›hastha AÅ›rama teachings contained inthe characterization of Sang Hyang Smara and Dewi Ratih show that a married couple must be able to maintain the relationship based on loyalty. The values contained in the story are the value of satyam (loyalty), the value of siwam (chastity) and the value of sundaram (beauty or the art) played by Sang Hyang Smara and Dewi Ratih.Â